DEVELOPING THE MATHEMATICS STUDENT ACTIVITY SHEET (SAS) IN SUBJECT MATTER SCALE AND COMPARISON FOR STUDENTS OF SMP CLASS VII BASED ON CURRICULUM 2013 - Edi Siswanto; Abdul Taram (Universitas Ahmad Dahlan, 2017)
This research is motivated by the lack of Student Activity Sheet (SAS) mathematics are using the curriculum 2013, particular in SMP Muhammadiyah 6 and 9 Yogyakarta as the learning process in the classroom. The purpose of this research is to develop a SAS based on curriculum 2013, determine eligibility based one matter expert assessment and teacher assessment, as well as student's response to SAS. The study was conducted through the model of Research and Development (R &D). Steps that passed include two aspects, namely the development of the SAS and its feasibility. SAS development includes: (a) collecting information (b) the designing of SAS (c) Validating SAS to the expert review by the mathematics teacher of SMP Muhammadiyah 6 Yogyakarta and SMP Muhammadiyah 9 Yogyakarta (d) revising the product. The feasibility of SAS include (a) trial test (b) data analysis (c) the feasibility of SAS. the subject's research was students SMP class VII. The results of research and development has developed the Student Activity Sheet (SAS) on the scale and comparison in class VII SMP based on the curriculum 2013. The results of matter experts assessment and teacher assessment on the obtained an average score of 82.5 with very good category, so the SAS can be declared feasible. The student's response to the SAS is included in very good categories indicated by an average score of 85.3225. These results indicate that the Student Activity Sheet (SAS) in the scale and comparison in classVII of SMP based on the curriculum 2013 can be used in the learning process.